APPLICATION OF THE MODERN TEACHING METHOD «SIX HATS OF THINKING» IN THE PROCESS OF TEACHING LITERATURE (EDUCATION IN THE 21ST CENTURY, 2025)
In the article entitled «The application of the modern teaching method «Six caps of thinking» in the process of teaching literature,» we tried to show the features of the application of the above method, due to the specifics of the taught material, the inclusion of ideological (worldview) issues, the possibility of different assessments of the topic under discussion, and the different opinions of students. We have considered the principles of applying the method in accordance with the substantive features of this method.  The essence of the above-mentioned method, the principles of teaching the material in this format are revealed with interesting accents; both the advantages due to the relevant features of this method of teaching and the features resulting from the purpose of teaching are indicated and justified.Using the «Six Hats of Thinking» method, the peculiarities of teaching individual literary works were emphasized. Within the framework of this teaching method, effective methods of analyzing literary works were considered, contributing to the multi-layered study of the taught material and the development of students' critical thinking.A number of advantages of using the method were emphasized: the multilayered interpretation of the issues discussed, the systematization of the material taught from different points of view, and a deeper understanding of the topic.
Keywords: caps of thinking; color counseling; critical and analytical thinking; posing ideological questions; psychological layers